Structural and Optical Properties of Samples SrTi\(_{1-x}\)M\(_{x}\)O\(_3\) (M = Co, Ni) Synthesized by Sol-gel Method - Phuong, Doan Thi Thuy; Minh, Nguyen Van; Dung, Chu Tien (Communications in Physics, 2013)
By sol-gel method, we synthesized SrTi\(_{1-x}\)M\(_{x}\)O\(_3\) (M = Co, Ni; x = 0.0; 0.1; 0.2; 0.3; 0.4; 0.5) nano particles and investigated structure of Raman spectrum, absorption spectra, structural diagram of energy area and their density of states. The results showed that the average size of nanoparticles was about 10-30 nm. Absorption edge of each sample depended on the content of substitution of Co, Ni.  Besides, the content of ion substitution also had influence on the structure, Raman  spectrum, structural diagram of energy area  and state density of samples. The results indicated that Co and Ni ions were substituted for position of Ti in the net cell, which changed structure of the material and reduced band gap of the synthesized materials and increases its conductivity.